Vertical tectonic motion in Andaman Islands detected by multi-temporal satellite radar images - Parcharidis, Is.; Foumelis, M.; Lekkas, E. (Bulletin of the Geological Society of Greece, 2007)
On 26 December 2004 one of the largest earthquakes ever recorded by modern seismology (Mw>9.0) occurred in Sumatra-Andaman region. About 1300km of seafloor were ruptured extending from northern Sumatra to Andaman Island complex. As instrumental data are sparse and in most of the cases field observations difficult to undertake, the role of remote sensing may be beneficial in providing information about the pattern of deformation in space and time. In the present study ENVISAT ASAR data are acquired and processed to generate a single multitemporal SAR image in order to detect vertical motion along Andaman Island. According to our analysis it seems that the northern parts of the island are generally uplifted. Though its north-western coasts show significant marL· of uplift, such indications become less evident along the western coasts of Middle Andaman. At some locations at the south-eastern margins of the island marks of downlift are recognized. Characteristic banding observed in the multi-temporal image could be attributed either to post-seismic relaxation, either to tidal phenomena. Although qualitative in nature, as just the sign of elevation change can be detected, results of such analysis could be used as constrains in deformation modelling research.